The biosocial subject: sensor technologies and worldly sensibility. Issue 2 (4th March 2018) - de Freitas, Elizabeth
ABSTRACT: Sensor technologies are increasingly part of everyday life, embedded in buildings (movement, sound, temperature) and worn on persons (heart rate, electro-dermal activity, eye tracking). This paper presents a theoretical framework for research on computational sensor data. My approach moves away from theories of agent-centered perceptual synthesis (on behalf of a perceiving organism) and towards a more expansive understanding of the biosocial learning environment. The focus is on sensor technologies that track sensation below the bandwidth of human consciousness. I argue that there is an urgent need to reclaim this kind of biodata as part of an unequally distributed worldly sensibility, and to thereby undermine more narrow reductive readings of such data. The paper explores the biopolitical implications of recasting biodata in terms of trans-individual inhuman forces, while continuing to track the distinctive power of humans.